Dendrogeomorphic reconstruction of past landslide activity in the Jablůnka village (Czech part of the Outer Western Carpathians) - Karel Šilhán (Revista de Geomorfologie, 2022)
Landslides represent an important and possibly very dangerous natural hazard. Dendrogeomorphic methods can provide unique data on the behaviour of landslides in the past by studying the tree-ring series of disturbed trees. Knowledge about past landslide activity in the flysch part of the Outer Western Carpathians is generally very scarce or missing. The past activity of selected landslides (possibly endangering neighbouring settlements) was studied using data from 106 increment cores from 53 disturbed individuals of Picea abies (L.) H. Karst. to assess its past spatiotemporal activity. In total, six certain event years and 13 probable events were detected during the period between 1927 and 2017. Certain events always occurred in groups of the two following events, suggesting the inertia of landslide movements after the initial triggering. The spatiotemporal reconstruction revealed a distinctly increased activity of movements in the zone of the main scarp and particularly in the landslide front, which could possibly endanger human infrastructure during its significant reactivation. However, the reconstruction performed suggests general landslide inactivity since 1997, when the last high-magnitude reactivation occurred.